Valproate Induced Acute Pancreatitis - A Unique Case Report - Chauhan, Vikramaditya; Sharma, Munish; Kapur, Ajita; Garg, Gulshan K. (Current Drug Safety, 2022)
Background: Valproate is a widely prescribed medication for the control of seizures in the pediatric population. It has been reported to be an important implication for drug induced pancreatitis. A case of valproate induced acute pancreatitis operated as surgical abdomen has been reported here. Case Report: A 13-year-old child presented to the emergency department with severe pain and abdominal distension associated with vomiting and constipation for four days. The patient’s caregivers did not disclose any medication history. Based on clinical examination and ultrasonography that revealed mild free fluid, a provisional diagnosis of pyoperitoneum with peritonitis was made. An emergency exploratory laparotomy was undertaken during which acute pancreatitis was diagnosed intra-operatively. On further enquiry, the caregiver revealed the history of valproate intake for the last six months for generalized tonic-clonic seizures. Valproate was discontinued and there was complete resolution of symptoms. Conclusion: Both clinicians, as well as caregivers of paediatric patients receiving valproate, should be watchful regarding this possible life-threatening complication to avoid delay in diagnosis and appropriate management.
Keywords: Valproate